Agustina em notas perigráficas (Philology, 2026)
The paper examines certain texts that are part and parcel of peripheral writing, or the perigraphy of Agustina Bessa-Luís. It deals with the way these texts, published by the Portuguese writer in the periphery of her fictional work, put into practice the self-reflection of Bessa-Luís when it comes to her own work as a writer and the very role of the writer. The definitions of “modern author” and “contemporary author” are problematized, as well as the idea of the writer as a carrier and disseminator of a whole ethos, or a set of moral, social, and emotional characteristics that are interconnected in a fixed way when it comes to perceiving and inhabiting the world.
Keywords: Agustina Bessa-Luís; perigraphy; writerly ethos